Leading change in the Capricorn District Municipality - Kganakga, Magobotla Daniel (My University, 2015)
Leading change in the Capricorn District Municipality (CDM) has been confronted with pressures of considering new mechanisms and strategies to deal with the imperatives of meeting service delivery targets as reflected in the Integrated Development Plan of the CDM. The devolution of water services and environmental health services functions to the municipality respectively meant that the municipality needed to reposition itself in order to respond to these emerging imperatives. In response, the CDM undertook a number of studies with the aim of developing an institutional development plan/road map. Following a qualitative paradigm, this study sought to investigate the factors that led to the unsuccessful implementation of several change management processes in the municipality. The study revealed that the recommendations of previously undertaken change management interventions were not implemented. Findings also revealed that there was a need for a change management framework to support change processes within the municipality. These issues found resonance in the approaches and models of leadership proposed by the researcher. These findings will then be juxtaposed with the lessons from Kotter’s Leading Change (1996) and Kouzes & Posner’s The Leadership Challenge: How to Get Extraordinary Things Done (1997). These two models are recommended as lessons that should be followed for successful implementation of change interventions. Highlights of the best practice on the African continent and internationally are given as lessons for leading change in the CDM.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.